Pengaruh ESG Tterhadap Harga Ssaham dengan Ukuran Perusahaan sebagai Variabel Moderasi - Davu Raissa Elazar; Maya Sari; Budhi Pamungkas Gautama (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
In this research, we use ESG Scores to examine how environmental, social, and governance (ESG) variables have affected the stock prices of companies listed on the Indonesia Stock Exchange. Using a quantitative approach that integrates descriptive and verification approaches, this research provides a thorough and trustworthy depiction of the connections between these variables. Companies for the sample were chosen using a purposive selection method. A Moderation Regression Analysis Test was used in this investigation. The study's findings demonstrate that ESG factors influence stock prices, which means the higher ESG score, the higher the share price. Following that, the impact of ESG on stock prices is mitigated by firm size which means that company size can affect the relationship between ESG and stock price. Companies should take environmental, social, and governance factors into account if they want to win over investors, according to this research. Companies that are good at making the most of their assets are main option for investors. The limitations of this study are the use of limited samples and variables also only focus on three main variables even though there are various other components that have the potential to affect stock prices. Suggestions for further research are to increase the study sample and add other variables that can affect stock prices. In addition, researchers can also increase the research period and use different subjects, so as to produce research findings that are new and more accurate.